Routine closure of the donor site with a second dorsal metacarpal artery flap to avoid the use of a skin graft after harvest of a first dorsal metacarpal artery flap. Issue 6 (June 2018) - Chi, Zhenglin; Lin, Damu; Chen, Yiheng; Xue, Jixin; Li, Shi; Chu, Tinggang; Li, Zhijie
Summary: Aim: Closure of the donor site on the index finger after raising a first dorsal metacarpal artery (DMA) flap harvest is challenging. The conventional choice is to use a full-thickness skin graft. However, this procedure is associated with several complications and a second donor site to harvest the skin graft is inevitable. The aim of this study was to design a modified incision to allow harvest of a first DMA flap without skin graft. Methods: From 2015 to 2016, 18 patients with a soft tissue defect of the thumb had reconstruction of the defect using a first DMA flap. A modified incision was used and a relaying perforator flap pedicled on the second DMA was raised through the same incision to cover the donor site. Patient satisfaction, appearance of the injured hand, and the active range of motion (ROM) were assessed. The sensitivity was evaluated by the 2-point discrimination (2-PD) test. Results: All flaps survived completely without complications. Good coverage was obtained with only one linear scar in the dorsum of the hand and no skin grafts. All patients recovered full range of movement in their fingers and regained sensitivity of the flaps. All patients were satisfied with their hand function according to the Michigan Hand Outcomes Questionnaire (MHQ). The mean cosmetic score for the appearance of the injured hand was 8.2 out of 10. Conclusions: Using our modified incision, it was possible to harvest a second DMA flap at the same time as a first DMA flap allowing simultaneous coverage of the donor defect on the index finger. This prevented the need for a skin graft with all of the associated disadvantages.